The effect of adding mint meal on some the chemical microbial and sensory properties of Syrian white cheese - سلطانة علي; سلمان فؤاد; قره علي أحمد; حلبي كاميليا (Latakia University Journal -Biological Sciences Series, 2021)
The study aimed to determine the effect of adding mint meal with two different concentrations (0.4, 0.7%) on some chemical and microbial characteristics of the lab-prepared cheese, as the cheese was made laboratory from cow’s milk pasteurized at a temperature of 72 m for 15 seconds by following the known traditional methods with adding mint powder to the curd. Cheese After filtering and with ratios (0.4, 0.7)% of the weight of the curd, the processed cheese samples were kept at a temperature of 4 ° C for 28 days, during which the samples were tested microbiology and chemically, and the results showed a significant effect of adding mint meal on some chemical and microbial properties compared to the control. Mint of cheese reduced the content of soluble and volatile nitrogen, and it also reduced the total number and the number of fungi and yeasts compared to the control cheese samples. Slightly prolonged storage time for cheese preserved without brine.